2017
DOI: 10.1007/s11136-017-1746-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the structural validity of the shoulder pain and disability index (SPADI) using the Rasch model

Abstract: Rasch Model analysis of the SPADI has identified some strengths and limitations not previously observed using CTT methods. The SPADI should be treated as two separate subscales. The SPADI is a widely used outcome measure in clinical practice and research; however, the scores derived from it must be interpreted with caution. The pain subscale fits the Rasch model expectations well. The disability subscale does not fit the Rasch model and its current format does not meet the criteria for true interval-level meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A Rasch model analysis of 1030 patients referred for physical therapy for shoulder pain also demonstrated a bidimensional structure; however, there was evidence of differential item functioning for some items in the disability subscale (eg, washing hair and putting on a shirt were more difficult for women than men, and putting on trousers was more difficult for people aged 60 or older). This suggests greater structural validity for the pain subscale than the disability subscale and implies that the two subscales should be reported separately (34).…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
See 1 more Smart Citation
“…A Rasch model analysis of 1030 patients referred for physical therapy for shoulder pain also demonstrated a bidimensional structure; however, there was evidence of differential item functioning for some items in the disability subscale (eg, washing hair and putting on a shirt were more difficult for women than men, and putting on trousers was more difficult for people aged 60 or older). This suggests greater structural validity for the pain subscale than the disability subscale and implies that the two subscales should be reported separately (34).…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
“…Factor analysis and Rasch modelling suggest that the SPADI should be treated as separate subscales; however, there may not be clear demarcation between underlying concepts in the two scales, and the disability subscale may not provide true interval‐level measurement (33,34). The upper anchor label for the disability subscale (so difficult it requires help) is potentially ambiguous because the perceived requirement for help may vary according to the level of help available to the individual respondent.…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
“…4,6 The suggested reason for this cross-loading of items is that functional tasks may be limited by pain making it difficult to differentiate between these two constructs. 46 49 Considering the results of the English SPADI and the translated versions the two-factor structure of the SPADI remains the dominant structure. If factor structure is not assessed in a translated study it is reasonable to assume, as many studies in this review have done, the two-factor structure for analysis of internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…This is the likely reason why previous studies have reported more of a unidimensional structure for the SPADI, especially where the pain construct is very high in conditions such as in adhesive capsulitis [25, 26]. A recent large randomised control trial and a multi-centre cohort study have provided further evidence of a two-factor structure for the SPADI, but even these studies suggest that the two factors of pain and disability are not well delineated with some items cross-loading [27, 28] and misfit of the disability items when the Rasch model is used [28].…”
Section: Discussionmentioning
confidence: 99%